INTERNATIONAL COMMERCIAL ARBITRATION: THEORETICAL AND LEGAL ASPECTS - Макеєва, Олена Миколаївна; Мудрик, Римма Русланівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Aim of the research: to study some theoretical aspects the emergence of such a legal phenomenon as arbitration. The concept of international commercial arbitration, which gets more popularity as an alternative dispute resolution and as body on trial the international commercial disputes, іs analyzed. The methodological basis of the research is the general scientific methods, complex and comparative methods. Results: the etymology of the concept of «arbitration» and «international commercial arbitration», criteria of differentiation the international courts and domestic courts of arbitration, international commercial arbitration and international arbitration are exposed in the article. Discussion: emphasize the importance of taking into account the historical formation of this institution and clarifying the etymology of the concept of international commercial arbitration. Arbitration as a phenomenon of independent justice arose at the beginning of the first civilizations of the world and became a prerequisite for the existence of state courts. International commercial arbitration has been and remains an effective and reliable alternative way of resolving foreign trade disputes. None of the sources of international law contains a unambiguous definition of arbitration. Only the UNCITRAL Model Law provides a detailed concept of international commercial arbitration, which is duplicated in Ukrainian law. The concept of international commercial arbitration should reflect its basic features. International Commercial Arbitration (ICAC) – any arbitration, regardless of what it creates for the consideration of individual cases (ad hoc), which is permanently operating in an existing arbitration institution, which provides consideration and resolution of international commercial disputes subject to a certain procedure. The term «commercial» refers to the nature of disputes that may be submitted to arbitration. The study of the legal nature and origin of «arbitration» plays an important role in understanding the essence of the arbitration process.